Pengaruh Hipnoterapi Terhadap Hasil Belajar Mata Kuliah Kecakapan Antar Personal - Miskanik, Miskanik (LANCAH: Jurnal Inovasi dan Tren, 2025)
This study aims to analyze the effect of hypnotherapy on student learning outcomes in the course Interpersonal Skills. This research uses a quantitative approach with an experimental design, where students who underwent hypnotherapy sessions were tested to observe changes in their learning outcomes. The data were analyzed using linear regression and correlation to identify the influence of hypnotherapy on the improvement of learning outcomes. The analysis results show that hypnotherapy has a significant positive effect on student learning outcomes, with a regression coefficient of 0.362 and a consistent correlation of 0.438. These findings suggest that hypnotherapy can improve students' interpersonal skills, reduce anxiety, and enhance concentration and self-confidence. Therefore, hypnotherapy can be an effective method to support learning, particularly for the development of interpersonal skills. This research provides valuable insights for educators to consider the implementation of hypnotherapy in a more holistic teaching strategy.